Kontestasi Kewenangan Komisi Yudisial sebagai Element of External Auditor dalam Proses Rekrutmen Hakim Agung - Andriani Larasati (Jurnal Hukum Lex Generalis, 2020)
The position of the Judicial Commission in the judicial institutions is now subject to degradation of the interpretation of authority in accordance with Article 24B Paragraph (1) of the Indonesia Constitution related to its role in selecting judges for the general judiciary, religion and state administration, through Decree No. 43/PUU-XIII/2015. The ruling changed the position and authority of the Judicial Commission into a judicial body that only functions in terms of oversight of ethical-professional issues against judges. The judicial commission's participation in the selection of judges with the aim of finding judges of integrity and professional integrity has been abolished. Based on these issues, the discourse on contestation of the authority of the Judicial Commission in the supreme court recusal process emerged as an urgency of discussion in the field of legal research on the Indepedency of External Auditors in judicial power in Indonesia.